Evaluation of the impact of the voucher and accreditation approach on improving reproductive health behaviors and status in Kenya - Warren, Charlotte (BioMed Central, 2011)
ABTSRACT: BACKGROUND: Alternatives to the traditional 'supply-side' approach to financing service delivery are being explored. These strategies are termed results-based finance, demand-side health financing or output-based aid which includes a range of interventions that channel government or donor subsidies to the user rather than the provider. Initial pilot assessments of reproductive health voucher programs suggest that, they can increase access and use, reducing inequities and enhancing program efficiency and service quality. However, there is a paucity of evidence describing how the programs function in different settings, for various reproductive health services. Population Council, funded by the Bill and Melinda Gates Foundation, intends to generate evidence around the 'voucher and accreditation' approaches to improving the reproductive health of low income women in Kenya. METHODS/DESIGN: A quasi-experimental study will investigate the impact of the voucher approach on improving reproductive health behaviors, reproductive health status and reducing inequities at the population level; and assessing the effect of vouchers on increasing access to, and quality of, and reducing inequities in the use of selected reproductive health services. The study comprises of four populations: facilities, providers, women of reproductive health age using facilities and women and men who have been pregnant and/or used family planning within the previous 12 months. The study will be carried out in samples of health facilities - public, private and faith-based in: three districts; Kisumu, Kiambu, Kitui and two informal settlements in Nairobi which are accredited to provide maternal and newborn health and family planning services to women holding vouchers for the services; and compared with a matched sample of non-accredited facilities. Health facility assessments (HFA) will be conducted at two stages to track temporal changes in quality of care and utilization. Facility inventories, structured observations, and client exit interviews will be used to collect comparable data across facilities. Health providers will also be interviewed and observed providing care. A population survey of about 3000 respondents will also be carried out in areas where vouchers are distributed and similar locations where vouchers are not distributed.